A Single Arm Clinical Study to Evaluate the Efficacy of Katankateriyadi Kwatha in the Management of Madhumeha (Diabetes Mellitus Type-2) (International Journal of Ayurveda and Pharma Research, 2025)
Madhumeha is known to Indian system of medicine since time immemorial. Almost all texts available, however old contain one or another very lucid hint of Prameha. This along with all of its causes, etiopathognesis, symptomatology, treatment and complications are mentioned in all Ayurvedic texts written centuries ago. It’s inclusion in eight major diseases (Astamahagada) indicates the significance and gravity attributed to it. Here 40 cases of newly diagnosed type 2 diabetes mellitus in a patient who underwent 3 follow up i.e., 30th, 60th, 90th of Katankateriyadi kwatha delivered in 3 months is reported. The patient’s fasting blood glucose and post plasma blood glucose levels, as well as HbA1C level were decreased after treatment. Further-more, no adverse effects were observed. The results of this clinical study are encouraging and provide evidence supporting the effectiveness of Katankateriyadi Kwatha in reducing Madhumha (Diabetes Mellitus Type-2) in a patient.